Assessment of entrepreneurial awareness as a factor of attitude of final year undergraduate students’ choice of entrepreneurship as a career option - Netshilinganedza, T. R.; Mudau, J.; Francis, J. (South African Journal of Higher Education, 2022)
A study that was designed to assess entrepreneurial awareness of final year undergraduate students as a factor of their attitude towards adopting entrepreneurship as a career choice was conducted at a rural area-based university in Limpopo Province of South Africa. A survey questionnaire was administered to 310 final year students registered for various degrees in the eight schools that constituted the university. The stratified random sampling technique was used to select the respondents. Crosstabulation, correlation analysis and Mann Whitney tests were carried out using the IBM Statistical Package for Social Sciences (SPSS) version 25.0. Entrepreneurial awareness among the students marginally influenced their attitudes towards a career in entrepreneurship. Overall, male and female students held similar views with respect to the influence of awareness of entrepreneurship among final year undergraduate students on their attitude towards self-employment (P > 0.05). It was recommended that management and policy interventions that created enabling conditions for nurturing students to become entrepreneurs should be adopted. Among the recommended interventions was the integration of entrepreneurship education into curricula, irrespective of areas of specialisation. This would equip the students with knowledge and develop positive attitude towards venturing into entrepreneurship.